Analysis on Water Wall Tube Explosion in a Power Plant. Issue 1 (June 2020) - Li, Yao; Liu, Chengming; He, Fengyuan; Wang, Fei
Abstract: Combined with the influencing factors of water wall tube explosion, this paper analyzes the water wall tube explosion of a power plant, and finds out that the water wall tube explosion may be caused by hydrogen embrittlement or local overheating, and expounds the measures to reduce the water wall tube explosion and reduce the risk of water wall tube explosion.